Development of Digital Comics Based on Culturally Responsive Teaching (CRT) to Improve Multicultural Competence and Sustainability Literacy - Neneng Kania Susi; Deddy Sofyan S; Yuyun Elizabeth Patras (Journal of General Education and Humanities, 2026)
Integrating the concepts of nature and the times into learning is a crucial foundation for creating education that is relevant to students' needs and current developments. Learning in accordance with nature, which takes into account student characteristics and instills social and cultural values, can support the development of multicultural competencies and sustainability literacy. Learning in accordance with the times facilitates the use of digital technology in learning media. The study aims to develop a digital comic based on Culturally Responsive Teaching (CRT) to improve multicultural competence and sustainability literacy in elementary school students. The method used is Research and Development (R&D) with the ADDIE model. The research design used was a one-group pretest-posttest. The research subjects were 30 fourth-grade students at an elementary school in Bogor Regency. The results of expert validation showed that the media was in the very feasible category, with 100% of media experts, 97% of material experts, and 98% of language experts. The results of the N-Gain test showed an increase in multicultural competence of 0.5825 and sustainability literacy of 0.6430 in the moderate category. Teacher and student responses indicated that the media was very practical. Thus, digital comics grounded in Culturally Responsive Teaching (CRT) are deemed feasible and practical for learning and highly effective in improving multicultural competence and sustainability literacy. This media can be an alternative solution for teachers in creating learning that is contextual and relevant to students' lives.